From sequence to function: analysis of Sox3 during early zebrafish development - Marelli, Elisa (2013)
Sox proteins are a family of transcription factors characterised by the presence of a conserved HMG box domain that mediates their binding to DNA. Ten groups of Sox proteins have been identified on the basis of their sequence similarities and named A-J. In particular, the SoxB1 subgroup is composed by highly conserved transcription factors that are involved in the differentiation of the cells towards a neural fate and the specification of neural tissue. During the embryonic development of several vertebrate species the first of the SoxB1 proteins to be expressed is Sox3, which is known to act both as a transcriptional activator and a transcriptional repressor at different stages of development. At the present time, little is known about the regulation of the balance between these two functions. Therefore, this study was aimed to identify the regions of Sox3 that are involved in its functioning as a repressor or as an activator. In order to meet this aim a deletion mutagenesis approach was developed to investigate how the deletion of different regions of Sox3 would have changed the protein’s function. A specific cloning strategy was designed in order to obtain twelve Sox3 deletion mutants, each carrying a deletion of about 20 amino acids, so that the regions deleted covered most of the protein sequence. The effects caused by the over-expression of each deletion mutant were then tested on zebrafish embryos and compared to the effects of over-expression of the wild type Sox3. Western blot analysis confirmed that microinjection of all the mutants into 1- 4 cell stage embryos, as well as microinjection of wild type sox3, resulted in similar levels of protein expression at sphere stage. The embryos microinjected with sox3 deletion mutants showed different phenotypes at 24 hours post fertilization (hpf), confirming that they affected the functioning of the protein differentially. In order to investigate deeper these functional changes, microinjected embryos were analysed at earlier stage of development. In zebrafish, Sox3 acts as a repressor of the organizer formation at sphere stage. Analysis of the effects of over-expression of Sox3 deleted mutants on the expression of the organizer marker genes bozozok and goosecoid, and the comparison with the effects caused by the over-expression of wild type Sox3, led to the identification of protein regions involved in Sox3 transcriptional repressor function. Analysis of the ability of Sox3 deletion mutants to induce the transcription of a luciferase reporter gene, compared to the wild type Sox3, allowed the identification of regions of Sox3 involved with its transcriptional activator function. The data obtained allowed us to draw a presumptive functional map of Sox3. The consistency of this map with evidence found in the literature led to the formulation of different hypotheses that would explain the functions associated with the regions identified. These promising data provide a basis for future studies, which will be aimed to the validation of the hypothesis formulated and to the identification of the amino acid residues that are responsible for the functions mediated by the regions identified.